ANN-based harmonic restraint differential protection of power transformer - Moravej Z.; Vishwakarma D.N. (My University, 2025)
This paper presents an ANN-based scheme for harmonic restraint differential protection of power transformer. This ANN-based scheme monitors different operating conditions of the transformer, detects the fault and issues the trip signal in the case of internal fault only. The proposed protection scheme is accurate, fast, efficient and reliable. This scheme has been realized through two different ANN structure using feed forward back propagation algorithm. The results amply demonstrate the capabilities of fault detector (FD) and condition monitor (CM) in terms of accuracy and speed with respect to detection of fault, and pattern recognition of different events of power transformer.